Pengaruh Pemberlakuan PPKM Darurat pada Masa Pandemi terhadap Penurunan Pendapatan UMKM di Desa Bandungsari Lamongan - Nasruddin Nasruddin; Riza Qomariyah Yansari (STEI Kanjeng Sepuh Gresik Jawa Timur, 2021)
The purpose of implementing the Emergency PPKM is to reduce the number exposed to the Covid-19 virus so that it can break the chain of tranmission. This study aims to examine the effect of implementing Emergency PPKM on the decline in UMKM income which was studies using the SPSS 16.0 data processing aplication, using 30 respondents consisting of business actors in Bandungsari village, Sukodadi District, Lamongan Regency. The results of the study indicate that there is an enterpreneurs during the Covid-19 pandemic due to regulations that limits operating hours to 20.000 WIB, provosions for eating and drinking in public places do not accept dine-in, eat on the spot and limited to only 50% delivery or take away visitors.